Brebes Buroq: The Art Expression of Coastal Javanese Moslem Society - Triyanto, Triyanto; Rokhmat, Nur; Mujiyono, Mujiyono; Sugiarto, Eko (Universitas Negeri Semarang, 2016)
The art of Buraq is a procession of puppet which has beautiful female face with winged-horse body and dance to the music of Genjring and tambourine. This traditional art is one of the dominant arts that becomes one cultural identity of the people in Brebes District, located in the west of the northern coast of Java island, Central Java Province. This study aims to study the aesthetic form, function and symbolic values of Buroq, as well as the system of relationship patterns among actors, Buroq puppets, and the audience. The result of the research shows that the rise of Buroq art stems from the Israâ-Miâraj â trip of Prophet Muhammad by using the vehicle named Buroq. It is narrated that Buraq is like a winged-horse with a beautiful woman face who can move with lightning speed as a vehicle in the Israâ-Miâraj journey of the Prophet Muhammad. This story is the primary source of inspiration for local artists to express aesthetic-symbolic in accordance with the imagination they possess in the form of acculturation that combines elements of Javanese, Chinese, and Islamic cultural symbols. As Islamic-based traditional arts of community, Buroq with all the uniqueness of its physical form not only has functions and values in the grandeur of Islam which awakens and strengthens the cultural awareness among residents to act and behave in accordance with the teaching of Islam in coastal Javanese Islamic culture but also has the functionality and entertainment value for the multicultural community.